1996
DOI: 10.1002/(sici)1099-0739(199611)10:9<727::aid-aoc547>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of Organic Arsenic Compounds in Marine Animals

Abstract: In the present study, we demonstrated for the first time the immunotoxic effects of organic arsenic compounds in marine animals, namely arsenocholine [AsCho; trimethyl(2‐hydroxyethyl)arsonium cation], arsenobetaine [AsBe; the trimethyl(carboxymethyl)arsonium zwitterion] and the tetramethylarsonium ion (TetMA), to murine principal immune effector cells (macrophages and lymphocytes), comparing them with the effects of inorganic arsenicals in vitro. Inorganic arsenicals (arsenite and arsenate) showed strong cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…However, an organic arsenic compound in marine animals, AsBe, was less toxic in thymocytes even at concentrations over 10 m M . Similar results were observed using PP lymphocytes; the percentage of the viability of PP lymphocytes incubated with 10 m M AsBe compared with that of control cells was 78.9±8.8%, and we previously reported that AsBe had no cytotoxicity in splenocytes even over 10 m M ( Sakurai et al ., 1996 ). These data imply that AsBe is less toxic in murine lymphocytes.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…However, an organic arsenic compound in marine animals, AsBe, was less toxic in thymocytes even at concentrations over 10 m M . Similar results were observed using PP lymphocytes; the percentage of the viability of PP lymphocytes incubated with 10 m M AsBe compared with that of control cells was 78.9±8.8%, and we previously reported that AsBe had no cytotoxicity in splenocytes even over 10 m M ( Sakurai et al ., 1996 ). These data imply that AsBe is less toxic in murine lymphocytes.…”
Section: Resultssupporting
confidence: 86%
“…In contrast, using the synthesized pure material, we demonstrated that the toxicity of AsBe in mammals is very weak. First, we reported that AsBe had no acute toxicity when it was orally administered to mice ( Kaise et al ., 1985 ) and also described that AsBe was not toxic in vitro in murine macrophages and splenocytes even at concentrations over 10 m M ( Sakurai et al ., 1996 ). Thus, we had been believed that AsBe had no biological effects, including toxic effects, in mammals.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations